DISKURSUS PEMBERDAYAAN MASYARAKAT - Faizal, Faizal (Universitas Islam Negeri Raden Intan Lampung, 2015)
Empowerment is the antithesis of the concept andimplementation of community development that hasbeen developed in the third world (developingcountries), including Indonesia. The concept andimplementation of development that is top down andmakes economic growth as the orientation onachieving a fair and equitable prosperity, has ignoredcommunity participation and fostertered dependency.Therefore, the empowerment that is people centered,participative and sustainable, can be used as alternativedevelopment model. And today empowerment as aparadigm, concepts and practices has been aninteresting discourse among theorists and academics aswell as practitioners and common public.